Conocimiento sobre bioseguridad de las enfermeras en el catéter venoso central en las áreas críticas - Escudero Castillo, Janet Raquel (2023)
This descriptive, quantitative, cross-sectional investigation was carried out with the objective of determining the level of knowledge of nurses about biosafety in the central venous catheter in critical areas of the Belén de Trujillo Hospital. The sample consisted of 40 nurses to whom the instrument was applied: a validated questionnaire to identify the level of knowledge of nurses about biosafety in the central venous catheter in critical areas. The statistical analysis was done using the SPSS version 25 statistical program, where a database was created in statistical tables with simple and percentage frequencies to determine the variable. The results show that the level of knowledge of nurses in the management of the central venous catheter 50.0% presented a medium level, referring to hand hygiene 55% with medium knowledge, in the use of personal protective equipment 57.5%. With a medium level of knowledge and about the elimination of biocontaminated waste, 50.0% obtained the medium level of knowledge